Microsystems for Cell Cultures - Iordania Constantinou (Biosensors, 2022)
Microfabricated systems are increasingly being utilized in biotechnological, biomedical, and pharmaceutical research and development as replacements for traditional in vitro cell cultures, bioreactors, and animal experiments (Figure 1) [...]